2017
DOI: 10.1139/cjpp-2017-0211
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mitochondrial properties may contribute to enhanced resistance to ischemia–reperfusion injury in the diabetic rat heart

Abstract: Diabetes mellitus, besides having deleterious effects, induces cardiac adaptation that may reduce the heart's susceptibility to ischemia-reperfusion (IR) injury. This study aimed to investigate whether changes in mitochondrial properties are involved in the mechanisms of increased resistance of the diabetic heart to IR. Adult male Wistar rats were made diabetic by a single dose of streptozotocin (65 mg·kg, i.p.), and on the day 8, Langendorff-perfused hearts were subjected to 30 min global ischemia and 40 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…To determine how pemafibrate may affect the myocardial IRI under diabetic conditions, the ultrastructure of the myocardium was evaluated in the present study and marked destruction of the intracellular structures were observed in the D-IRI group. Similar alterations about myocardial injury and mitochondrial dysfunction in the diabetic IRI have been observed in other reports (25,26). In vivo analysis in the present study demonstrated that pemafibrate partially restored the mitochondrial structure in the myocardium.…”
Section: Discussionsupporting
confidence: 91%
“…To determine how pemafibrate may affect the myocardial IRI under diabetic conditions, the ultrastructure of the myocardium was evaluated in the present study and marked destruction of the intracellular structures were observed in the D-IRI group. Similar alterations about myocardial injury and mitochondrial dysfunction in the diabetic IRI have been observed in other reports (25,26). In vivo analysis in the present study demonstrated that pemafibrate partially restored the mitochondrial structure in the myocardium.…”
Section: Discussionsupporting
confidence: 91%
“…These findings point to respiratory-chain damage as a result of the metabolic consequences of diabetes. On the other hand, in the acute phase of diabetes, experimental animals exhibited decreased vulnerability to ischemia [49], reperfusion injury [50,51], and calcium overload [52]. The latter finding was attributed to the increased rigidity of the sarcolemmal membrane due to intensified non-enzymatic glycation of membrane proteins, which decreases the mobility of membrane components and affects the permeability properties of the lipid bilayers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, compared with STEMI patients with DM, patients without DM have stronger reaction to acute ischemic injury and are more prone to IRI ( 11 ). Muráriková’ s team believed that because the heart of DM patients may adapt to the changes caused by DM and increase tolerance to ischemic injury, the recovery of DM patients after IRI is better than that of patients without DM, with fewer cardiovascular events ( 12 ). However, there are also different research results on the relationship between DM and IRI in clinic.…”
Section: Discussionmentioning
confidence: 99%